2013
DOI: 10.1074/jbc.m113.484576
|View full text |Cite
|
Sign up to set email alerts
|

An Undesired Effect of Chemotherapy

Abstract: Background: CXCR4 signaling protects pancreatic cancer cells from gemcitabine toxicity. However, the effect of gemcitabine on this resistance mechanism is unclear. Results: Gemcitabine up-regulates CXCR4 expression in pancreatic cancer cells and promotes their invasiveness. Conclusion: CXCR4 signaling serves as a counterdefense mechanism against gemcitabine. Significance: These findings are significant for the formulation of effective therapeutic strategies against pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 41 publications
9
81
0
Order By: Relevance
“…Moreover, our data demonstrated that both Akt and ERK played an important role in mediating the effect of PAK4 on subcellular localization of NF-κB/p65 and its transcriptional activity. This is consistent with our recent finding, where we have delineated the cooperative involvement of Akt and ERK pathways in the activation of NF-κB/p65 [40]. In another report, ERK has been identified as a downstream effector pathway mediating PAK4-induced pro-survival effects [41].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, our data demonstrated that both Akt and ERK played an important role in mediating the effect of PAK4 on subcellular localization of NF-κB/p65 and its transcriptional activity. This is consistent with our recent finding, where we have delineated the cooperative involvement of Akt and ERK pathways in the activation of NF-κB/p65 [40]. In another report, ERK has been identified as a downstream effector pathway mediating PAK4-induced pro-survival effects [41].…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, the recent studies revealed that CXCR4 is correlated with different degree of chemosensitivity of a variety of cancer types, including chemosensitivity of panceatic cancer to GEM[11-15]. Some researches has implicated some miRNAs (like miR-21, miR-200, miR-145) and p85 in the regulation of drug resistance of pancreatic cancer to GEM[1, 8, 16-18].…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine induces intracellular production of reactive oxygen species (ROS) in pancreatic cancer cells, although the contribution of ROS to gemcitabine-induced cancer cell killing is still controversial [38,39]. The study by Donadelli et al showed that gemcitabine-induced ROS plays a role in gemcitabine-mediated cytotoxicity in pancreatic cancer cells, since NAC blunted ROS production and protected cells against gemcitabine toxicity [38].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Donadelli et al showed that gemcitabine-induced ROS plays a role in gemcitabine-mediated cytotoxicity in pancreatic cancer cells, since NAC blunted ROS production and protected cells against gemcitabine toxicity [38]. In contrast, a recent study by Arora et al concluded that gemcitabine-induced ROS production contributed to NFκB-mediated gemcitabine resistance, which was reversed by NAC in MIA PaCa-2 cells in vitro [39]. Although this study was performed in cultured cells, its data support our conclusion that gemcitabine-induced NFκB activation contributes to gemcitabine associated chemo-resistance in vivo (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation